Acceptability of two perturbation-based balance training paradigms: perturbation treadmill versus dynamic stability training in the presence of perturbations - Hezel, Natalie; Brüll, Leon; Arampatzis, Adamantios; Schwenk, Michael (Gerontology, 2024)
Introduction: Perturbation-based balance training (PBT) is promising for fall prevention in older adults, mimicking real-life fall situations at a person’s stability thresholds to improve reactive balance. Hence, it can be associated with anxiety, but knowledge about the acceptability of PBT is scarce. Method: This is a secondary analysis of a randomized controlled trial comparing the effects of two different PBT paradigms that aims to evaluate and compare the acceptability of those training paradigms in fall-prone older adults. Participants (74.9 ± 5.7 years) who completed the training (6 weeks, 3x/week) on either a perturbation treadmill (PBTtreadmill: n = 22) or unstable surfaces in the presence of perturbations (PBTstability: n = 27) were surveyed on the acceptability of PBT using a 21-item questionnaire addressing seven domains (perceived effectiveness, tailoring, demand, safety, burden, devices, affective attitude), based on the theoretical framework of acceptability and context-specific factors. Relative scores (% of absolute maximum) for single items and domains were calculated. Results: Median domain scores of perceived effectiveness, tailoring, safety, devices, and affective attitude were all ≥70% for both paradigms. The highest scores were obtained for tailoring (both paradigms = 100% [interquartile range 80-100%]). Domain scores of demand and burden were in the medium range (40-45%) for both paradigms. No significant differences between paradigms were found for any domain score. Two single items of safety differed significantly, with PBTtreadmill perceived as needing less support (p = 0.015) and leading less often to balance loss (p = 0.026) than PBTstability. Conclusion: PBT conducted on a perturbation treadmill or unstable surfaces is well accepted in this fall-prone older sample, even though it is conducted at individual stability thresholds. Tailoring may play a key role in achieving high levels of perceived effectiveness, appropriate levels of demand and burden, and a high sense of safety. PBT delivered on treadmills might be more appropriate for more anxious persons.
Gesehen am 28.10.2024